1997
DOI: 10.1097/00007890-199702270-00013
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Children Less Than Two Years Old1

Abstract: Twenty-one infants, 2 years old or younger, received 21 renal transplants between 1983 and 1995. Six of the transplantations were performed from 1983 to 1989, and the remaining 15 were performed from 1990 to 1995. The median age at transplantation was 16.0 months and the median body weight was 9.0 kg. Living-related donor kidneys were used in 15 cases, an adult cadaveric donor kidney was used in one case, and pediatric cadaveric donor kidneys were used in five cases. All grafts were placed intra-abdominally. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Many centers have reported catch-up growth after TX in children <5 years of age [22][23][24][25], and this is supported by our findings. It is also in agreement with the large NAPRTCS (North American Pediatric Renal Transplant Cooperative Study) registry report, in which catch-up growth after TX was seen primarily in the youngest age groups [26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many centers have reported catch-up growth after TX in children <5 years of age [22][23][24][25], and this is supported by our findings. It is also in agreement with the large NAPRTCS (North American Pediatric Renal Transplant Cooperative Study) registry report, in which catch-up growth after TX was seen primarily in the youngest age groups [26].…”
Section: Discussionsupporting
confidence: 90%
“…In many earlier reports, "catchdown" growth was seen a few years after TX. Although not reported in detail, it seems to be related to deterioration of graft function with time [25,30]. As we and other authors have shown, the youngest recipients receiving an adult graft do not maintain their long-term graft function in response to body growth [15,16,25].…”
Section: Growth Hormone Therapymentioning
confidence: 57%
See 1 more Smart Citation
“…It is evident that small patients benefit with respect to their mental and physical development. Lerner et al [1], for example showed that early kidney transplantation can prevent growth retardation [1, 2, 3, 4, 5]. Living donor transplantation should be performed whenever a suitable donor is available, especially for children with a severe underlying disease, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, a successful renal transplantation results in the normal mental and physical development of a child. Thus, even very young children with end–stage renal failure are being referred for consideration of a renal transplant [1, 2, 3, 4, 5, 6]. From the surgical point of view, small children remain a problematic patient group as the discrepancy between graft and recipient vessels may lead to various surgical complications.…”
Section: Introductionmentioning
confidence: 99%